Performance analysis of 2D optical code division multiple access through underwater wireless optical medium - Islam, Md. Rabiul; Islam, Md. Jahedul; Mitra, Bithi; Hossain, Md. Amzad; Islam, Jahedul; Dev, Shuvo (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The performance of a two-dimensional optical code division multiple access (2D-OCDMA) system using an underwater wireless optical (UWO) medium is assessed in this work. The optical source is an LED with a working wavelength of 532 nm, and the optical detector is a p–i–n photodiode. When calculating the bit error rate (BER), the phase-induced intensity noise (PIIN), thermal noises, and shot sounds are taken into account. The user code address is set using 2D perfect difference (2D-PD) codes. Link distance, inclination angle, beam divergence angle, transmitter power, and the number of concurrent users are all taken into account when determining the BER performance. For various water media, such as pure sea water (PSW), clear ocean water (CLOW), and coastal ocean water (CSOW), the performance of the suggested system is examined.